A Comparative Analysis of School and Student Characteristics on Bullying in Urban Career Academies and a Large Comprehensive High School. (3rd April 2021) - Fletcher, Edward C.; Tan, Tony Xing
ABSTRACT: In this study, we examined the relationship between school type and students' victimization and observations of bullying in their schools. We compared student perceptions ( N = 1, 283) of bullying in three urban career academies with different school configurations (e.g., magnet and school-within-a-school) and a large, urban comprehensive high school. We found that compared to their counterparts in the large comprehensive high school, students in two of the career academies – operated as magnet schools – were significantly less likely to experience bullying as a victim or to observe it in their respective schools. However, compared to students in the comprehensive high school, there were no significant differences in bullying among students in the career academy operated under a school-within-a-school model. It is plausible that students in career academies that operate as magnet schools are significantly less likely to become victims and observe bullying.